Can Uttaranchal Become a Tourist Paradise? The Relation between Resources and Infrastructure - Singhal, P. N; Raghavan, G; Pal, Surinder (Journal of Commerce and Trade, 2007)
The fruits of economic development fall where educated people live, not where they work. Hence, if we want to enrich villages, we should induce the educated to live there. But for this to happen we need to install reliable means of social services and transport and other systems that are on a par with what is available in the cities. Uttaranchal is blessed with magnificent glaciers, majestic snow-clad mountains, gigantic and ecstatic peaks, valley of flowers, skiing slopes and dense forests, this Abode of Gods includes many shrines and places of pilgrimage. Char-dhams, the four most sacred and revered Hindu temples: Badrinath, Kedarnath, Gangotri and Yamunotri are nestled in the Mighty Mountains. A picturesque state, with a breathtaking panoramic view of Himalayas, Uttaranchal promises its tourists a visit full of fun and unforgettable moments. It would appear that the road map for tourism development in Uttaranchal state is after all not that difficult. What we may need is only be a commitment for its development from the local government - which ever political party is mandated to rule the state.